Calmodulin and calmodulin-like gene family in barley: Identification, characterization and expression analyses - Cai, Kangfeng; Kuang, Liuhui; Yue, Wenhao; Xie, Shanggeng; Xia, Xue; Zhang, Guoping; Wang, Junmei (Frontiers in Plant Science, 2022)
Calmodulin (CaM) and calmodulin-like (CML) proteins are Ca2+ relays and play diverse and multiple roles in plant growth, development and stress responses. However, CaM/CML gene family has not been identified in barley (Hordeum vulgare). In the present study, 5 HvCaMs and 80 HvCMLs were identified through a genome-wide analysis. All HvCaM proteins possessed 4 EF-hand motifs, whereas HvCMLs contained 1 to 4 EF-hand motifs. HvCaM2, HvCaM3 and HvCaM5 coded the same polypeptide although they differed in nucleotide sequence, which was identical to the polypeptides coded by OsCaM1-1, OsCaM1-2 and OsCaM1-3. HvCaMs/CMLs were unevenly distributed over barley 7 chromosomes, and could be phylogenetically classified into 8 groups. HvCaMs/CMLs differed in gene structure, cis-acting elements and tissue expression patterns. Segmental and tandem duplication were observed among HvCaMs/CMLs during evolution. HvCML16, HvCML18, HvCML50 and HvCML78 were dispensable genes and the others were core genes in barley pan-genome. In addition, 14 HvCaM/CML genes were selected to examine their responses to salt, osmotic and low potassium stresses by qRT-PCR, and their expression were stress- and time-dependent. These results facilitate our understanding and further functional identification of HvCaMs/CMLs.